2004
DOI: 10.3189/172756504781830213
|View full text |Cite
|
Sign up to set email alerts
|

The flow of Fireweed rock glacier, Alaska, U.S.A.

Abstract: Fireweed rock glacier is a large rock glacier in south central Alaska, U.S.A. It flows relatively fast, with velocities up to 3.5 ma–1, and exhibits both seasonal and annual velocity variations, some of which are related to periodic terminus calving and increased rainfall. Our analysis reveals that motion is likely concentrated in a pseudo-rectangular channel within the larger parabolic channel with a “shear plane” at ~27 m depth. There is likely motion along the shear plane as well as internal deformation abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…In contrast to the strength of polycrystalline ice and frozen soils derived from laboratory tests, the huge Fireweed rock glacier in Alaska had surface velocity fields requiring A values at least twice those of clean temperate ice [ Bucki and Echelmeyer , 2004]. The high A values indicating soft frozen ground appear to be associated with the large amount of debris, which was in fact seen at the calved front [ Elconin and LaChapelle , 1997; Bucki et al , 2004].…”
Section: Factors Affecting Deformation Of Ice‐debris Mixturementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the strength of polycrystalline ice and frozen soils derived from laboratory tests, the huge Fireweed rock glacier in Alaska had surface velocity fields requiring A values at least twice those of clean temperate ice [ Bucki and Echelmeyer , 2004]. The high A values indicating soft frozen ground appear to be associated with the large amount of debris, which was in fact seen at the calved front [ Elconin and LaChapelle , 1997; Bucki et al , 2004].…”
Section: Factors Affecting Deformation Of Ice‐debris Mixturementioning
confidence: 99%
“…The high A values indicating soft frozen ground appear to be associated with the large amount of debris, which was in fact seen at the calved front [ Elconin and LaChapelle , 1997; Bucki et al , 2004]. Bucki and Echelmeyer [2004] considered that the large A values originated from interstitial water between debris particles and ice crystals, which possibly allowed slip at the interface by lowering the effective viscosity, as Echelmeyer and Wang [1987] and Cohen [2000] explained the softness of dirty basal ice. Cohen [2000] proposed quite large A values (1.4 × 10 −14 –1.4 × 10 −13 kPa −3 s −1 ) for dirty basal ice below a 210 m thick temperate glacier by means of a three‐dimensional simulation.…”
Section: Factors Affecting Deformation Of Ice‐debris Mixturementioning
confidence: 99%
“…Most of these studies documented that increasing debris concentration resulted in strengthening over the full range of concentrations, in contrast with Swinzow's observations [ Goughnour and Andersland , ; Baker , ; Ting et al, ; Ladanyi and Morel , ; Durham et al, ]. However, a few laboratory studies and several field studies have concluded that debris concentrations less than about 42% by volume can sometimes lead to significant weakening [ Hooke et al , ; Echelmeyer and Zhongxiang , ; Bucki and Echelmeyer , ; Song et al ., ]. To explain these apparently contradictory observations, some researchers have appealed to the potential influence of unfrozen water concentration with or without solutes [ Cohen , ; Cuffey et al ., ], particle size, or ice crystal size [ Fisher and Koerner , ; Cuffey et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…). The maximum velocities on California rock glacier, however, are insignificant in comparison with some > 300 cm/yr displacements that have been observed on the Fireweed rock glacier in Alaska and on some rock glaciers in the Austrian Alps(Bucki and Echelmeyer 2004; Krainer and Mostler 2006). In the Elk Mountains of Colorado, flow rates averaged 63 cm/yr from1964 -1968(Bryant 1971.…”
mentioning
confidence: 83%
“…Warm ice can flow more quickly or meltwater can act as a lubricant and reduce friction between internal shear planes (Bucki and Echelmeyer 2004;Krainer and Mostler 2006;Ikeda et al 2008). Rock glaciers typically have a debris cover (1-3 m thick in some instances), which acts as an insulator and protects internal ice.…”
Section: Jason R Janke and Antonio Bellisariomentioning
confidence: 99%